1993
DOI: 10.1212/wnl.43.7.1389
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic acid–A new therapeutic approach to peroxisomal‐disorder patients

Abstract: Docosahexaenoic acid (DHA, 22:6 omega 3) is a major constituent of brain membrane phospholipids and photoreceptor cells. Patients with generalized peroxisomal disorders have extremely low levels of DHA in the brain and other tissues. Since a DHA deficiency could explain some basic symptoms in peroxisomal-disorder patients, we tested the possible beneficial effects of DHA in two patients with neonatal adrenoleukodystrophy (NALD). Before the treatment, both patients had very low DHA levels in plasma and erythroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1

Year Published

1995
1995
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 0 publications
1
29
1
Order By: Relevance
“…In addition, a potential beneficial effect on visual functions and myelination could not be evaluated in the newborn mouse. We did not observe changes either in plasmalogen levels or in C26:0 levels in brain of DHA-treated Zellweger mice, which is in contrast to the findings in DHA-treated Zellweger patients (Martinez et al, 1993). It should be noted that in the patients, plasmalogens and C26:0 were analyzed in erythrocytes and in plasma, respectively, whereas in DHA-treated mice, the phospholipid fraction of the brain was used.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…In addition, a potential beneficial effect on visual functions and myelination could not be evaluated in the newborn mouse. We did not observe changes either in plasmalogen levels or in C26:0 levels in brain of DHA-treated Zellweger mice, which is in contrast to the findings in DHA-treated Zellweger patients (Martinez et al, 1993). It should be noted that in the patients, plasmalogens and C26:0 were analyzed in erythrocytes and in plasma, respectively, whereas in DHA-treated mice, the phospholipid fraction of the brain was used.…”
Section: Discussioncontrasting
confidence: 96%
“…In several of the Zellweger patients treated with DHA by Martinez (Martinez, 1996;Martinez et al, 1993), the increase of DHA levels was accompanied by an increase of the vinyletherphospholipids (plasmalogens) in erythrocytes and a decrease of C26:0 levels in plasma. Analysis of the brain phospholipid fraction of DHA-treated PEX5 Ϫ/Ϫ mice revealed that the plasmalogen levels were somewhat increased but remained extremely low (Table 1) and that C26:0 accumulated to the same extent as in non-treated PEX5 Ϫ/Ϫ mice (Table 1).…”
Section: Supplementation Of Dha To Pex5 ؊/؊ Fetusesmentioning
confidence: 99%
“…Administration of pure ethyl-docosahexae-noate (Et-DHA) to two patients with one of these syndromes, neonatal adrenoleukodystrophy, resulted in almost complete normalization of the biochemical profile and a profound, albeit partial, therapeutic effect (Martinez et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Deficiency of DHA is considered to relate to brain and visual dysfunction and abnormal myelination. 54,55 Although 11 human PEX genes have been identified, there are over 20 yeast PEX genes. Novel complementation groups and responsible genes may be elucidated in the near future.…”
Section: Pathophysiology Of Pbdsmentioning
confidence: 99%